Analisis Kesiapan Guru Dalam Mengimplementasikan Kurikulum Merdeka Di Era Digital - Ahya Mahfuzah; Sahar Wardani; Dwi Umul Hasanah; Hidyatu Munawaroh (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
The Merdeka Curriculum is an educational initiative introduced by the Indonesian government with the aim of providing freedom and flexibility in the learning process in schools. This research aims to explain and provide an overview of understanding regarding teacher readiness in implementing the independent curriculum in the current digital era. This research uses a qualitative approach method with a case study type of research. This research was carried out at Sutogaten State Elementary School with research subjects in class IV of Sutogaten State Elementary School and the class teacher. The object of this research is a form of readiness in implementing independent curriculum learning. The instruments used in this research used interview, observation and questionnaire guidelines. The results of this research show that teachers still need to learn a lot and need training regarding the Independent Curriculum, that in using the new curriculum, teachers need to adapt to the curriculum that is being used.